Unusual presentation of Rosai-Dorfman disease in a 14-month-old Italian child: a case report and review of the literature. Issue 1 (December 2016) - di Dio, Francesco; Mariotti, Ilaria; Coccolini, Elena; Bruzzi, Patrizia; Predieri, Barbara; Iughetti, Lorenzo
Abstract Background Rosai-Dorfman disease (RDD) is a rare form of histiocytosis characterized by histiocyte proliferation within lymph nodes and extranodal tissue. Here we report an unusual presentation of RDD in an Italian toddler. Moreover, we reviewed the pediatric case reports published between 2004 and 2014, focusing in particular on medical therapy. Case presentation We report the case of a 14-month-old child who developed a progressive swelling of the right parotid, associated with systemic symptoms and abnormal blood tests. During diagnostic work-up, cervical, intraparotid, and unilateral hilar lymphadenopathies were found. Histopathological and immunohistochemistry studies of a cervical lymph node biopsy established the diagnosis of RDD, with positive PCR for Epstein - Barr virus on the biopsy specimen. Oral steroid therapy was started with progressive reduction in size of all lesions, resolution of systemic symptoms, and normalization of blood tests. Conclusion RDD is generally considered a benign and self-limiting form of histiocytosis, usually associated with favorable prognosis. However, complications are not infrequent and fatal cases were reported even in children. Efforts should be made to establish the best therapeutic strategy for this disease, as no well-defined guidelines exist. Finally, RDD should be included in differential diagnosis of lymphadenopathy and parotid swelling even in very young children.